The relationship between music training and cognitive flexibility: an ERP study - Hao, Jiayi; Zhong, Yuhuan; Pang, Yazhi; Jing, Yuanluo; Liu, Yong; Li, Hong; Li, Jianbo; Zheng, Maoping (Frontiers in Psychology, 2023)
Music training involves several cognitive functions in the brain, particularly executive function. Numerous studies have proven a link between the two. Cognitive flexibility is an important component of executive function, however, there has been little study investigating the association between music training and cognitive flexibility. Music training (N=22) and the control groups (N=26) were included in the present study. A tone-related oddball task was used to investigate the tone-related inhibition and the switch task was to investigate cognitive flexibility. During the switch task, EEG data were collected. The behavioral results of the oddball task showed that the individuals in the music training group had a shorter reaction time and higher accuracy in both the between-tone and within-tone categories compared to the controls. The behavioral results of the switch task showed similar results, with the music training group exhibiting better reaction time and accuracy performance than the controls. ERP results showed that the music training group had smaller P3 amplitudes and greater N2 and N450 amplitudes than the control group. The findings further supported the link between music training and enhanced cognitive function.